2019
DOI: 10.1155/2019/4504302
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis and Iron Homeostasis in Non-Transfusion-Dependent Thalassemia Patients with Extramedullary Hematopoiesis

Abstract: Background. Extramedullary hematopoiesis (EMH) is common in non-transfusion-dependent thalassemia (NTDT) patients. Clinical presentations of EMH vary as MRI screening is not feasible. Hence, serum biomarkers are used to predict the risk of EMH. Materials and Methods. 52 NTDT patients, including 26 EMH (+) and 26 EMH (-), together with 26 healthy controls, were enrolled in this case-control study from 2013 to 2016. EMH was confirmed by computed tomography or MRI. Demographic, transfusion, genetic, laboratory, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
3
9
2
1
Order By: Relevance
“…It needs to be further elucidated whether biological effects of ERFE and GDF15 in MDS are restricted to the regulation of iron metabolism and iron supply to proliferating erythroid progenitors. Although previous studies reported correlations between ERFE and GDF15 circulating levels with parameters of iron metabolism, 8,26,27 no strong correlations between ERFE and GDF15 expression in erythroid progenitors in MDS and available iron parameters were observed in our study. The correlation between ERFE expression and haemoglobin levels was very weak (Spearman r = −0·2322).…”
Section: Discussioncontrasting
confidence: 99%
“…It needs to be further elucidated whether biological effects of ERFE and GDF15 in MDS are restricted to the regulation of iron metabolism and iron supply to proliferating erythroid progenitors. Although previous studies reported correlations between ERFE and GDF15 circulating levels with parameters of iron metabolism, 8,26,27 no strong correlations between ERFE and GDF15 expression in erythroid progenitors in MDS and available iron parameters were observed in our study. The correlation between ERFE expression and haemoglobin levels was very weak (Spearman r = −0·2322).…”
Section: Discussioncontrasting
confidence: 99%
“…In thalassemia, ineffective erythropoiesis induces the release of factors including growth differentiation factor 15 (GDF15), twisted gastrulation protein homolog 1 (TWSG1), Hypoxia Inducible Factor (HIF), and erythroferrone (ERFE), which can all inhibit hepcidin release. A negative correlation of GFD 15 with hepcidin corroborates the suppression of the iron regulatory protein and hepcidin [28] . Data of the present study illustrated the the presence of a significant negative correlation between serum ferritin and age of thalassemia onset, frequency of blood transfusions, as when hemolysis present early, this will need more frequent blood transfusions, which lead to significant elevation in serum ferritin level and ultimately iron overload.…”
Section: Discussionmentioning
confidence: 58%
“…Yumei Huang et al. reported a mean age of 27.5 years [ 25 ]. EMH is related to chronic and prolonged anaemia that leads to ineffective erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%